Precipitation and mean streamflow reconstruction on Piaxtla River based on tree-ring width series from Pseudotsuga menziesii (Mirb.) Franco - Villanueva Díaz, José; Gómez Guerrero, Armando; Estrada Ávalos, Juan; Martínez Sifuentes, Aldo Rafael (Instituto de Ecología, A.C., 2020)
The hydroclimatic reconstruction is relevant to understand how a forest watershed works and take decisions about its management. In this study the precipitation and streamflow on Piaxtla river watershed was reconstructed, using tree-ring width index values from Pseudostuga menziesii. From seven dendrochronological series, a regional series (RS) was built. The correlation of RS with ocean-atmosphere phenomena like El Nino/Southern Oscillation, Pacific Decadal Oscillation, Atlantic Multidecadal Oscillation, and Palmer Drought Severity Index was tested. Results showed the reliability of reconstructing the November-April precipitation and the November-August streamflow from the early wood series with verified and validated equations: Precipitation = -271.538 + 447.764*(Early wood index), (r = 0.85, n = 49, p < 0.0001) and Streamflow = 5.123 + 0.623*(log10(Early wood index)), (r = 0.68, n = 46, p < 0.001). Except for the Atlantic Multidecadal Oscillation, all climate circulatory events had significant correlation to the dendrochronological information. This study confirms the high sensibility of P. menziesii in the Sierra Madre Occidental reflected in a high correlation among tree-ring width series and hydroclimatic variables. For this reason, the potential of this study should be expanded to monitor any change in the availability of water resources and for the valuation of hydrological environmental services.